Investigating the relationship between menopausal women's health anxiety and sexual performance and attitude towards menopause - Raziyeh Malaijerdi; Leila Amini; Hamid Haghani; Homa Sadeghi Avval Shahr (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Menopause is a natural event in the life of women. Women's concerns during menopause and the role of health anxiety in the attitude and sexual performance of women during this period affect the quality of life. Therefore, the present study was conducted with the aim of determining the relationship between health anxiety and sexual performance and attitude towards menopause in postmenopausal women. MATERIALS AND METHODS: The present study was a cross-sectional study of communication type that was conducted on 200 postmenopausal women with records in Sabzevar Comprehensive Health Centers in 2021-2022. In order to collect information, standard questionnaires of health anxiety, attitude towards menopause, and sexual performance were used. The collected data were analyzed by SPSS version 16 software and descriptive and analytical statistical tests (Spearman). A significance level of less than 0.05 was considered. RESULT: The results of data analysis showed that health anxiety has a significant relationship with the dimensions of desire (p = 0.045 and r = −0.142) and sexual pain (p < 0.001 and r = 0.274). Also, there was a significant relationship between the attitude towards menopause with sexual performance (p < 0.001 and r = 0.244) and health anxiety with the attitude towards menopause (p < 0.001 and r = 0.27). CONCLUSION: The results of this study showed that there is an inverse relationship between health anxiety and sexual desire and a significant direct relationship with sexual pain. Also, the attitude towards menopause has a significant direct relationship with sexual behavior and health anxiety. Therefore, it is suggested to pay attention to the mental health of postmenopausal women along with the physical aspect and to pay attention to educational programs to improve the care and health programs of these women.